Market orientation for better accountability of government-linked companies / Jamaliah Said … [et al.] - Said, Jamaliah; Alam, Md. Mahmudul; Abdullah, Nik Herda; Zulkarnain, Nur Nadiah (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study assesses the status of the current level of market orientation among the Government-Linked Companies (GLCs) in Malaysia. This study collected primary data based on a set of questionnaire survey among 134 executives and managers of GLCs in Malaysia. The data were collected based on the opinions of the ten factors of market orientation practices by using the five-point Likert scale. The data were analyzed using descriptive statistics. On an average, 86.6% of the respondents agreed that they focus on these factors of market orientation. The federal-owned GLCs placed more emphasis on market orientation than the state owned GLCs. This study suggests improving the practices of market orientation of GLCs in Malaysia by emphasizing on providing close attention to after-sales service, responding rapidly to the threats of competitive actions, regularly discussing the competitors’ strengths and strategies by the top management, and freely communicating successful and unsuccessful customer experiences across all business functions. It is suggested that Malaysian GLCs should seriously invest in market orientation to deliver high accountability outcomes.